2015
DOI: 10.1002/srin.201400354
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of Fluoride‐Free Boracic Mould Flux for Steel Continuous Casting

Abstract: Development of fluoride-free mould flux is important for steel continuous casting. Properties of the mould flux depend on the flux crystallinity. This paper analyzes phase composition of fluxes containing B 2 O 3 , TiO 2 , Na 2 O, and MgO which can be feasible candidates to replace the fluorides. The phase equilibria of these fluoride-free boracic mould fluxes were calculated using the thermochemical software FACTSage. In the process of crystallization of the CaO-SiO 2 -Al 2 O 3 -B 2 O 3 -Na 2 O flux with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…On the contrary, mold flux FF-D showed single crystalline for all cooling rates regardless of atmosphere, as shown in Figure 4. Based on an independent XRD measurement for the quenched sample of FF-D slag at 1100 K (827°C), this crystalline phase has been identified to be merwinite (3CaO-MgO-2SiO 2 ), which corresponds to the study carried out by Cui et al [14] It is found that the change of primary crystalline phase from cuspidine to Ca 2 SiO 4 would be the main reason for acceleration of melt crystallization under wet atmosphere. This implies that evaporation of fluorine will govern the phase and kinetics of melt crystallization in this study.…”
Section: ½5mentioning
confidence: 70%
“…On the contrary, mold flux FF-D showed single crystalline for all cooling rates regardless of atmosphere, as shown in Figure 4. Based on an independent XRD measurement for the quenched sample of FF-D slag at 1100 K (827°C), this crystalline phase has been identified to be merwinite (3CaO-MgO-2SiO 2 ), which corresponds to the study carried out by Cui et al [14] It is found that the change of primary crystalline phase from cuspidine to Ca 2 SiO 4 would be the main reason for acceleration of melt crystallization under wet atmosphere. This implies that evaporation of fluorine will govern the phase and kinetics of melt crystallization in this study.…”
Section: ½5mentioning
confidence: 70%
“…Many metallurgists have done a lot of theoretical and practical research about the continuous casting breakout, which plays an important role in the development of efficient continuous casting. On the one hand, it is generally believed that sticker breakout forms near the meniscus due to the poor lubrication and excessive friction [2][3][4]. It is closely related to factors, such as molten steel composition [5] and mould powder [6,7], and also influenced by the mould level, casting speed and manual operation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that sticker breakouts are initially formed near the meniscus. The poor lubrication and excessive friction of the strand shell are the direct cause of sticker [1][2][3], which are also closely related to factors, such as molten steel composition, mould flux, casting speed, mould level, and manual operation [4,5].…”
Section: Introductionmentioning
confidence: 99%